2019
DOI: 10.1038/s41598-019-45428-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue is linked with attentional bias for sad stimuli

Abstract: Previous studies have revealed that patients with chronic fatigue syndrome and affective disorders (such as depression and anxiety disorders) exhibit a vigilant attentional bias toward negative emotional stimuli. However, it remains unclear whether the change in an attentional bias for negative emotional stimuli can be induced by mental fatigue in healthy individuals. To address this question, we examined healthy participants’ (n = 27) performance in a visual probe task and emotional Stroop task before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Unlike previous alcohol-related studies, in which the instructions revealed the overall objective of the study (e.g., attention processing), one of the common features in all three experiments was that VAT was presented to the participants as a false memory task: such strategy intended to provide a fairly stable framework of exploration of the images, therefore avoiding the fact that lengthy cognitive tasks may be linked with mental fatigue [42]. However, the impact of a false memory task on the performance of an attention-related task remains unexplored: the authors of the current research hypothesize that presenting the VAT as a false memory task may have enhanced selective attention and working memory processing as a result of the exploration strategy (intention to memorize as many elements as possible).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous alcohol-related studies, in which the instructions revealed the overall objective of the study (e.g., attention processing), one of the common features in all three experiments was that VAT was presented to the participants as a false memory task: such strategy intended to provide a fairly stable framework of exploration of the images, therefore avoiding the fact that lengthy cognitive tasks may be linked with mental fatigue [42]. However, the impact of a false memory task on the performance of an attention-related task remains unexplored: the authors of the current research hypothesize that presenting the VAT as a false memory task may have enhanced selective attention and working memory processing as a result of the exploration strategy (intention to memorize as many elements as possible).…”
Section: Discussionmentioning
confidence: 99%
“…The poor dietary habits, harsh living environment, and negative mental stimulation could cause serious health problems [ 19 21 ]. Studies have shown that changes in intestinal microbiota link poor dietary habits to Alzheimer's disease [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…FI dataset [27] was obtained through filtering 90,000 noisy images collected from Flicker and Instagram, and 225 AMT workers performed the filtering. Although some qualification tests to filter workers who just want to get paid for completing the task and do not perform the task seriously have been designed, fatigue due to the repeated labeling tasks can cause stress to workers, which may greatly affect their emotional perception of the images [24]. In contrast, by using game, our method enable players to evaluate images in a more relaxing and enjoyable way, and hence more reliable results can be expected.…”
Section: Affective Image Annotationmentioning
confidence: 99%